Sustainability risk management: are Malaysian companies ready? - Abdul Razak, Shazrul Ekhmar; Mustapha, Mazlina; Mohammed Shah, Sabarina; Abu Kasim, Nor Aziah (Elsevier, 2024)
The sustainability issues resulting from Malaysian palm oil production have garnered much interest in the palm oil industry. Consequently, Malaysian palm oil industry is indirectly exposed to sustainability risks, including boycott and reputational and regulatory risks. Hence, the industry encounters intense pressure from numerous stakeholders to address sustainability issues. Prior studies propounded that sustainability risk management (SRM) could minimise the adverse impact of sustainability risks by addressing sustainability issues. Nevertheless, the implementation of sustainability risk management in Malaysia remains low as numerous companies are not ready for it. Drawing on contingency theory, the objective of this study is to investigate the influence of contextual factors that can influence companies' readiness in implementing sustainability risk management. Data was collected through the distribution of questionnaires between July and December 2020. A total of 407 questionnaires were distributed, with a response rate of 29 . Resultantly, sustainability strategy, business size, top management support, and regulatory pressure positively and significantly influenced sustainability risk management implementation. The findings also expanded the current theoretical knowledge with valuable insights for policymakers regarding the factors influencing to companies’ readiness in implementing SRM.